Impact of cardiac rehabilitation on pre- and post-operative transcatheter aortic valve replacement prognoses - Zou, Jieru; Yuan, Jie; Liu, Jingjin; Geng, Qingshan (Frontiers in Cardiovascular Medicine, 2023)
Transcatheter aortic valve replacement (TAVR) is a relatively new treatment method for aortic stenosis (AS) and has been demonstrated to be suitable for patients with varying risk levels. Indeed, among high-risk patients, TAVR outcomes are comparable to, or even better, than that of the traditional surgical aortic valve replacement (SAVR) method. TAVR outcomes, with respect to post-surgical functional capacity and quality of life, have also been found to be improved, especially when combined with cardiac rehabilitation (CR). CR is a multidisciplinary system, which integrates cardiology with other medical disciplines, such as sports, nutritional, mind-body, and behavioral medicine. It entails the development of appropriate medication, exercise, and diet prescriptions, along with providing psychological support, ensuring the cessation of smoking, and developing risk factor management strategies for cardiovascular disease patients. However, even with CR being able to improve TAVR outcomes and reduce post-surgical mortality rates, it still has largely been underutilized in clinical settings. This article reviews the usage of CR during both pre-and postoperative periods for valvular diseases, and the factors involved in influencing subsequent patient prognoses, thereby providing a direction for subsequent research and clinical applications.